The potency of red onion skin flavonoids in acetaminophen-induced liver injury management: A biomolecular review - Radya Kusuma Ardianto; Lucky Dimas Abimanyu; Afif Wafiq Waliyuddin; Abi Noerwahjono; Dian Yuliartha Lestari; Fathiyah Safithri (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Acetaminophen is widely used as a fever and pain reliever drug. However, acetaminophen intoxication was common and responsible for thousands of acetaminophen-induced liver injury (AILI) cases worldwide. It was understood that glutathione (GSH) depletion causes a deposit of acetaminophen metabolites which are toxic to liver cells. N-acetylcysteine (NAC), used as acetaminophen intoxication therapy, has been reported to cause side effects such as nausea, vomiting, and anaphylactic reaction. This narrative review aimed to discuss other potential candidates in AILI management. The biomolecular approach was used to investigate onion skin in-depth and holistic discussion. According to the results, onion peel extract is rich in flavonoids (quercetin and kaempferol) and potentially be a candidate in the management of AILI through proposed mechanisms such as restoration of reduced glutathione (GSH), inhibition of cytochrome P450 (CYP) enzymes, upregulation of uridine 5'-diphospho-glucuronosyltransferase (UGT) enzyme, and inhibition of TLR4 activity.